1992
DOI: 10.2118/19399-pa
|View full text |Cite
|
Sign up to set email alerts
|

Improved Data-Analysis Method Determines Archie Parameters From Core Data (includes associated paper 24964 )

Abstract: We present a data-analysis approach to determine Archie parameters m and n from standard resistivity measurements on core samples. The analysis method, core Archie-parameter estimation (CAPE), results in computed water saturations that agree well with core-measured saturations. CAPE determines m and n by minimizing the error between computed and measured water saturations. The conventional method minimizes the error in nonphysical quantities. Also, CAPE provides a natural, physically meaningful method of "aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…(4) by plotting "Sw" vs "resistivity index". Maute et al (1991) introduced a mathematical technique to determine Archie's parameters m,n and optionally a from standard resistivity measurements on core samples. The idea of this technique is to determine the Archie's parameters by minimizing the mean square error between the measured and the computed saturations using the Archie' Equation.…”
Section: Conventional Determination Of a M And Nmentioning
confidence: 99%
“…(4) by plotting "Sw" vs "resistivity index". Maute et al (1991) introduced a mathematical technique to determine Archie's parameters m,n and optionally a from standard resistivity measurements on core samples. The idea of this technique is to determine the Archie's parameters by minimizing the mean square error between the measured and the computed saturations using the Archie' Equation.…”
Section: Conventional Determination Of a M And Nmentioning
confidence: 99%
“…Among the various methods available in the literature, Core Archie-Parameters Estimation (CAPE) (Maute et al 1992;Enikanselu and Olaitan 2013), which is an analysis method, is to estimate the Archie parameters a, m and n by minimizing the error between the computed water saturation and the measured water saturation. It is observed that the regressions of I R D S n w vs Sw and F vsˆbased on their plots are not the optimum way to obtain the Archie parameters.…”
Section: The Model Of Cape (Core Archie-parameters Estimation)mentioning
confidence: 99%
“…In (Maute et al 1992), a data analysis approach is proposed to determine the Archie parameters m; n and a based on standard resistivity measurements on the core samples. The simplex method is applied in (Chen et al 1995) to identify the three parameters of Archie equation.…”
Section: Introductionmentioning
confidence: 99%
“…Core Archie-Parameter Estimation (CAPE) Maute et al (1992) have presented a data analysis approach to determine Archie's parameters m and n and optionally n from standard resistivity measurements on core samples. The analysis method, Core Archie-Parameters Estimation (CAPE) determines m and n and optionally a by minimizing the error between computed water and measured water saturations.…”
Section: Conventional Determination Of a And Mmentioning
confidence: 99%